Analisis Kinerja Jaringan Internet Menggunakan Mikrotik dengan Backbone Fiber Optik dengan Metode QoS - Nofrizal Nofrizal; Arif Rizki Marsa; Zulkifli Zulkifli (STMIK Pringsewu, 2022)
Designing a backbone in the network can overcome several problems that occur, such as speed problems connected between local networks because UTP cables can only be passed with transfer speeds of up to 100 Mbps, while the backbone network is capable of loading up to 10 Gbps. The design and installation of the internet network will be carried out at several Regional Government Organizations (OPD) in the city of Payakumbuh so that the internet network with a backbone can be utilized optimally to improve services to the community. The network performance will be analyzed using the Quality of Service (QoS) method which includes latency, jitter, packet loss, and throughput. QoS is defined as a mechanism that allows services to operate according to the characteristics of the Internet Protocol (IP) network. The results of this study are the value of measuring the performance of the fiber optic backbone network carried out at the Capil (OPD) Capil, Bappeda, and the Department of Transportation. With the QoS method, the results of the tests that have been carried out in the morning, afternoon, and evening are obtained.